Ovarian steroid cell tumor, not otherwise specified, during pregnancy - Reyna-Villasmil, Eduardo (2021)
Ovarian steroid cell tumors are classified into stromal luteoma, Leydig cell tumor and steroid cell tumor not otherwise specified, according to their embryonal origin. Ovarian steroid cell tumor not otherwise specified is a rare benign tumor, but with malignant potential; it accounts for less than 0.1% of all ovarian tumors. They should be considered as a cause of virilization in adult women due to testosterone production. Only a female fetus is at risk of virilization. Like other ovarian stromal tumors, the tumors must be treated surgically. Surgery is indicated in cases of solid unilateral ovarian enlargement, due to a 50% chance of malignancy. In pregnancy, ovarian steroid cell tumors not otherwise specified are exceptionally rare and should be differentiated from luteoma of pregnancy and other malignant ovarian neoplasms. More frequently they may be complicated by rupture and/or torsion. A case of nonspecific ovarian steroid cell tumor during pregnancy is presented.